Predictors of satisfaction and quality of life following post‐mastectomy breast reconstruction. Issue 11 (6th March 2017) - Matthews, Hannah; Carroll, Natalie; Renshaw, Derek; Turner, Andrew; Park, Alan; Skillman, Jo; McCarthy, Kate; Grunfeld, Elizabeth A.
Abstract: Objective: Breast reconstruction is associated with multiple psychological benefits. However, few studies have identified clinical and psychological factors associated with improved satisfaction and quality of life. This study examined factors, which predict satisfaction with breast appearance, outcome satisfaction and quality of life following post‐mastectomy breast reconstruction. Methods: Women who underwent post‐mastectomy breast reconstruction between 2010 and 2016 received a postal questionnaire consisting of The BREAST‐Q Patient Reported Outcomes Instrument, The European Organisation for Research and Treatment of Cancer QLQ‐30 Questionnaire, The Patient and Observer Scar Assessment Scale, and a series of Visual‐Analogue Scales. One hundredforty‐eight women completed the questionnaire, a 56% response rate. Results: Hierarchical multiple regression analyses revealed psychosocial factors accounted for 75% of the variance in breast satisfaction, 68% for outcome satisfaction, and 46% forquality of life. Psychosocial well‐being emerged as a significant predictor of satisfaction with breast appearance (β = .322) and outcome satisfaction (β = .406). Deep inferior epigastric perforator flap patients reported greater satisfaction with breast appearance (β = .120) and outcome satisfaction (β = .167). Conclusions: This study extends beyond the limited research by distinguishing between satisfaction with breast appearance and outcome satisfaction. The study provides evidence for the role of psychosocial factors predicting key patient reported outcomes and demonstrates the importance of psychosocial well‐being and reconstruction type. The findings also highlight the need for healthcare providers to consider the psychosocial well‐being of patients both preoperatively and post operatively and provide preliminary evidence for the use of deep inferior epigastric perforator reconstructions over other types of reconstructive procedures.